0D modeling aspects of flame stretch in spark ignition engines and comparison with experimental results. (1st October 2016) - Demesoukas, Sokratis; Brequigny, Pierre; Caillol, Christian; Halter, Fabien; Mounaïm-Rousselle, Christine
Highlights: A 0D model is proposed to take into account flame stretch effect in SI engine. Simulations were compared to optical engine experiments to validate the model. Flame stretch can affect the burnt mass fraction and the in-cylinder pressure prediction. Laminar flame speed needs to be considered as a function of stretch in SI engine. Abstract: With the different kinds of fuel now available, modern spark ignition engines have to be adapted, owing not only to the difference between the characteristic heat of combustion of the different fuels, but also to the response of the flame to stretch. As the burning rate is a function of the laminar burning speed which is a function of the flame stretch, this parameter has to be taken into account by combustion models. In this study, a zero-dimensional combustion model, based on the Flame Surface Density equation, is enhanced with a model for the stretched laminar burning speed. Numerical results are compared with the experimental results of three lean air-fuel mixtures with isooctane, propane and methane as fuels, that have similar unstretched laminar burning speeds but different Lewis numbers. Laminar burning speed, flame radius, burnt mass fraction, and turbulent flame wrinkling are compared with experimental results. The simulation trends are similar to those of experimental results. Methane and propane (Lewis number 0.99 and 1.80 respectively) show similar wrinkling rates, while isooctane (Lewis number 2.90) has a lower wrinkling rate. The observed difference between computed burnt mass fraction with stretched and unstretched flame speed models reveals that the impact of stretch and Lewis number needs to be taken into account and that a stretched laminar burning speed must be used for modeling, especially for mixtures with a Lewis number much greater than unity.